Indazole Derivatives Effective against Gastrointestinal Diseases - Saha, Supriyo; Pal, Dilipkumar; Nimse, Satish B. (Current Topics in Medicinal Chemistry, 2022)
Background: In this fast-growing lifestyle, humans are in the race against time to cope up with busy schedule. Less exercise, consumption of high calorie-low fiber food and stress take us one step closer towards digestive dysfunction. Dysfunctional digestive system causes various gastrointestinal disorders like constipation, IBS, UC, diarrhea, gastrointestinal tract immobility, hyperglycemia, hemorrhoids, fistula, anal fissures, stomach cancer, hepatocellular carcinoma, pancreatic cancer, colon cancer and metabolic syndrome. Amongst various natural and synthetic indazole derivatives nigellicine, nigellamine, nigellidine, zanubrutinib and SCH772984 showed prominent results to cure various gastrointestinal disorders. Objectives: In this manuscript, we focus on the importance of indazole derivatives in the treatment of various gastrointestinal diseases. Results and Conclusion: In the treatment of IBS, four positions (R1, R2, R3 and R4) of indazole were mainly substituted with aromatic aldehyde/substituted methyl, aromatic acid/formamide, benzamide/ sulfonamide and methyl groups, respectively. In case of diarrhea and metabolic syndrome treatment, substitutions with benzyl/isopropyl/acetaldehyde (R1 position) and carboxamide/ formamide (R2 position) of indazole play a critical role. Also, in the treatment of diabetes melitus, all six positions of indazole derivative were substituted with substituted aryl/alkyl/aromatic acid, substituted formamide, substituted acetamide/hydrazide group, halo aryl, substituted aryl/aromatic acid and a long chain of alkyl-aryl alcohol groups, respectively. In the treatment of gastrointestinal cancers, all six positions of indazole derivative were substituted with benzylamide (R1), octanediamide/ benzamide/formamide (R2), carbaldehyde (R4) and substituted phenyl (R5 and R6) groups, respectively. Six receptors (6NP0, 2YME, 4EFU, 4WZ8, 5U4W and 7KKP) associated with GI disorders (co-crystallized with indazole derivative) were identified. Analysis of the receptors showed that co-crystalized ligand molecules were well-interacted with receptors via pie-pie interaction, coordinate and sigma bonding within 4 Å distance. As per Ramachandran plot analysis, more than 90% of the amino acid residues were present in the most favored region. So, if sufficient focuses are imposed on the development of newer indazole derivatives to treat gastrointestinal diseases, it will work as a boon to society.
Keywords: Metabolic syndrome